The Effectiveness of E-Books as a Media for Developing Digital Literacy Skills: A Literature Study - Zahro, Aulia; Sari, Dinda Hafna (Proceeding International Conference on Education, 2025)
Literacy is an individual's ability to speak and communicate effectively according to context and purpose. This study aims to examine the effectiveness of using e-books as a medium that can support the development of digital literacy. The approach used is a literature study, by analyzing various scientific literature related to the use of e-books in the context of digital literacy. The results show that e-books have great potential in improving digital literacy skills because they are interactive, easy to access, and flexible to use at any time. E-books also support students in accessing information independently and critically. However, limitations include the lack of standardized content quality and the lack of assistance in their use, especially for students with low digital skills. Therefore, this study recommends the development of integrated and user-friendly e-books as effective digital literacy media to improve 21st century literacy competencies.